NXTHVN - Rosenthal, Jean, active 2021; Cooney, Kate; Elias, Jaan (London : Yale School of Management, 2019)
NXTHVN, artist Titus Kaphar's vision, combined a new type of art incubator with a community center. Could he find a sustainable way to prepare emerging artists and invigorate a neighborhood? Could NXTHVN provide a model for others? Titus Kaphar was a highly successful artist. One dominant theme of his work was creative reuse of classical images to expose hidden relationships of race and subjugation. When he moved back to New Haven, Connecticut, he began a project that required creative reuse and reframing on a much grander scale. He co-founded an organization, NXTHVN, to take an old factory building in a rundown neighborhood and reconfigure the space into an art incubator, artists' studios, and a community center.
Originally Published InRosenthal, J., Cooney, K., & Elias, J. (2019). NXTHVN. 19-017. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Artists and community; Social responsibility of business; Sustainability